The Role of Woman Cadre in Organizations - Yudieth Sry Lestari (International Journal on Social Science, Economics and Art, 2020)
This research tries to describe and analyze how woman's role in North Sumatra HMI Badko organization. There is a semi-autonomous institution in HMI organization that put its woman's cadres in a special position. The semi-autonomous institution called Kohati. Kohati was formed as a forum to facilitate women cadres in order their contribution to the HMI greater. Additionally, Kohati shaped to women cadres in the organization do not feel marginalized its existence by a cadre of men who are more numerous than the women cadres This is a descriptive study with the aim to give an overview of the situation by using qualitative analysis. Data collection techniques used in this research is the data collection techniques derived directly from the source through the results of interviews with researchers using primary data sources and supported by secondary data. The theory used in this study is the role of theory, the theory of cadres, gender theory and organizational theory. Role theory is used to position a person in accordance with a given social position either formally or informally. Cadres theory is used to fully understand the policy and ideological struggle of the organization to be able to implement a consistent struggle at all times, situations and places. The gender theory is used to identify the difference of male and female is viewed in terms of social and cultural conditions, values ​​and behavior, mentality and emotions as well as other nonbiological factors. Organizational theory can be used as a political system because the organization is made up of internal support that attempts to control the decision-making process in order to improve their position. The results of this study are conducted by empowerment Kohati in improving the quality of life of women, especially the quality of its cadres. Empowerment done through the provision of access to lectures, seminars on women, cadre training and leadership training. Kohati also examines gender issues that exist in society. In addition to improving the quality of women's roles, Kohati roles in increasing women's economies and political. Gender equality in North Sumatra HMI Badko organization has manifested itself in the division of roles and structural positions. But gender equality happens only superficially. Women only occupy positions such as treasurer and secretary. In addition, the role of women in decision-making was assessed as weak because the number of women in this organization is still small.